2017
DOI: 10.1194/jlr.m075432
|View full text |Cite
|
Sign up to set email alerts
|

A new enzyme-linked immunosorbent assay system for human serum hepatic triglyceride lipase

Abstract: There is no established method for measuring human hepatic triglyceride (TG) lipase (HTGL) concentration in serum. In this study, we developed new monoclonal Abs (MoAbs) (9A1 mouse MoAb and 141A1 rat MoAb) that react with HTGL both in serum and in postheparin plasma (PHP) and established a novel ELISA system for measuring serum HTGL and PHP-HTGL concentrations. To confirm the specificity of MoAbs, we performed immunoprecipitation-immunoblotting analysis. Both 9A1 mouse MoAb and 141A1 rat MoAb were able to immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…A Human GPIHBP1 Assay Kit (IBL) based on sandwich ELISA was used to determine serum GPIHBP1 concentrations [36]. Finally, the Human Serum HTGL ELISA Kit (IBL) was used to measure serum HTGL concentrations [34].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Human GPIHBP1 Assay Kit (IBL) based on sandwich ELISA was used to determine serum GPIHBP1 concentrations [36]. Finally, the Human Serum HTGL ELISA Kit (IBL) was used to measure serum HTGL concentrations [34].…”
Section: Methodsmentioning
confidence: 99%
“…In the past, owing to the low sensitivities of assays, previous methods used for measuring circulating activities and concentrations of lipases required heparin administration. Therefore, assay methods based on the monoclonal antibodies against these lipases have been developed recently to achieve sufficient sensitivities for measurement of serum LPL and HTGL concentrations without the need for heparin administration [3234]. As a result, preheparin serum LPL concentrations can now be measured using a latex particle-enhanced turbidimetric immunoassay with an automated analyzer [35], and preheparin serum HTGL concentrations can be determined using high-sensitivity HTGL enzyme-linked immunosorbent assay (ELISA) [34].…”
Section: Introductionmentioning
confidence: 99%
“…The serum EL concentration was measured using the EL-ELISA (enzyme linked immunosorbent assay) developed by Ishida et al 20) . Serum HL concentration was determined by HL-ELISA developed by Miyashita et al 12) . Serum LPL concentration was measured by LPL-ELISA described by Shirakawa et al 21) .…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that low plasma HL activity is associated with hypertriglyceridemia and CAD 10, 11) . However, high serum HL concentration is associated with increased CAD risk 12) . LPL is mainly expressed in adipose tissue, skeletal, and cardiac muscle, and catalyzes the hydrolysis of triglycerides in circulating lipoproteins 5) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation